Shifting boundaries in professional care. - Hopkins, A (1996)
The nature of the work undertaken by different health professionals and inter-professional boundaries are constantly shifting. The greater knowledge of users of health care, and the increasing technical and organizational complexity of modern medicine, have partly eroded the control of health professionals over the substance of their work. The definition of a field of work as lying within the province of any one profession is culturally rather than scientifically determined. It is evident that care of good quality should be delivered at the lowest possible cost. This might include delivery of care by a less trained person than heretofore, or by someone with limited but focused training. Sharing of skills is a more sensible subject for discussion than transfer of tasks. We review a number of studies which show the effectiveness of inter-professional substitution in various care settings, and also the effectiveness of substitution by those other than health professionals. The views of users of health services on inter-professional substitution need to be considered. Health professionals and others need to work together to devise innovative ways of delivering effective health care. The legal issues need clarification.